TAFSIR ILMI DAN GEOLOGI; ANALISA USIA BUMI - Achmad Zubairin (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2023)
This paper is an attempt to connect the interpretation of the Qur'an with science. This paper agrees with the interpreters/ulama who agree with scientific interpretation, both with inductive and deductive approaches. Among the scholars who agree with scientific/scientific interpretations are Al-Ghazali, Muhammad Abduh, Al-Maraghi, Thantawi Jauhari, Sa'id Hawa. Their argument is that verses that talk about the universe must be approached from a scientific perspective. This paper disagrees with Al-Syathibi and Ibn Taimiyyah who oppose this scientific/'ilmi interpretation, those who are too concerned about the Al-Qur'an will lose its miracle if the scientific theory adopted into the interpretation of the Al-Qur'an changes. By using qualitative methods in research, this paper aims to apply scientific analysis in interpretation. Based on the results of scientific experiments conducted, it turns out that many scientific hints were found in the Al-Qur`an, so that the continuity of life on this earth is maintained.